2021
DOI: 10.1038/s41598-021-89221-4
|View full text |Cite
|
Sign up to set email alerts
|

Response of Nagpur mandarin (Citrus reticulata Blanco) to high density planting systems

Abstract: High density planting system i.e. accommodating a higher number of plants than routine in a given area is an innovative agro-technology to increase yield and thereby early net returns. Due to conventional wide spacing plantation in Nagpur mandarin (Citrus reticulata Blanco), the land remains unutilized as the plant canopy gradually increases over the years. In the present study, Nagpur mandarin (Citrus reticulata Blanco) budded on Rangpur lime rootstock was evaluated under six different planting spacings. It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 15 publications
0
5
0
2
Order By: Relevance
“…O aumento do volume de copa por hectare se deve ao maior número de plantas, conferido pelos espaçamentos menores, já que o volume individual das copas não diferiu entre os tratamentos. O maior volume de copa está relacionado positivamente com maior interceptação da radiação fotossinteticamente ativa incidente na área (Ladaniya et al, 2021), o que proporcionou maior produtividade por hectare da comunidade de plantas de Ponkan/FD. Costa et al (2021) concluíram que a produtividade estimada em porta-enxertos selecionados de híbridos de Sunki e FD dobraria para uma média de 40 t ha -1 por ano se o espaçamento das árvores fosse ajustado para o menor tamanho da copa.…”
Section: Resultsunclassified
“…O aumento do volume de copa por hectare se deve ao maior número de plantas, conferido pelos espaçamentos menores, já que o volume individual das copas não diferiu entre os tratamentos. O maior volume de copa está relacionado positivamente com maior interceptação da radiação fotossinteticamente ativa incidente na área (Ladaniya et al, 2021), o que proporcionou maior produtividade por hectare da comunidade de plantas de Ponkan/FD. Costa et al (2021) concluíram que a produtividade estimada em porta-enxertos selecionados de híbridos de Sunki e FD dobraria para uma média de 40 t ha -1 por ano se o espaçamento das árvores fosse ajustado para o menor tamanho da copa.…”
Section: Resultsunclassified
“…Hence, their productivity was always lower: Valencia sweet oranges on allotetraploid Swingle citrumelo rootstock at 1000 trees•ha −1 accumulated only 153 t•ha −1 from 2014 to 2020, even with a 40% increase over 513 trees•ha −1 , while trees on IAC 1710 at 513 and 1000 trees•ha −1 accumulated 286 and 367 t•ha −1 , respectively (Table S3). This clearly demonstrated that productive rootstocks are crucial to boost citrus productivity in the subtropics, with the advantage of causing minimal impact on the production cost compared with increasing tree density [20,22,67].…”
Section: Increasing the Tree Density Work Best As Long As Highly Productive Rootstocks Are Availablementioning
confidence: 92%
“…Regardless of its potential to boost early productivity, high-tree-density plantings require greater investment and may lead to the reduction of yield due to excessive tree crowding and difficulties in operations [22]. To address such limitations, the tree size control has been evaluated in high-density citrus orchards, including the use of pruning [23], training systems [24], irrigation [25], and dwarfing rootstocks [26].…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, orchards of Wase satsuma mandarin with a density of up to 10,000 plants ha −1 were evaluated via long-term tests [ 23 ]. Recent research conducted in India with Nagpur mandarin on Rangpur lime rootstock determined that a high-density planting was regarded as one that included between 555 and 625 plants ha −1 and that an ultra-high-density planting was considered as one that contained between 1250 and 2500 plants ha −1 [ 13 ]. Therefore, long-term experiments will be needed to examine commercial citrus cultivars with dwarfing rootstocks to determine optimal plant density under modern production circumstances.…”
Section: Planting Density For Citrus Rootstocksmentioning
confidence: 99%
“…High-density (HD) planting systems are an innovative approach that helps improve yield, and net returns, particularly in the early stages of orchard development, by accommodating more plants per unit area than traditional planting systems [ 13 ]. Precocity, low cost per unit production and the potential for higher mechanization with improved input use efficiency are the main benefits of intensive cultivation systems.…”
Section: Introductionmentioning
confidence: 99%